Flame-retardant cellulose aerogel reinforced resin material as well as preparation method and application thereof

By constructing cellulose aerogel coating on the resin surface, the problems of low flame retardant performance and complex preparation of carbon fiber composites are solved, and efficient flame retardant performance improvement and strength maintenance are achieved. It is suitable for enhanced modified plastics, construction and electric heating field.

CN119192647APending Publication Date: 2024-12-27CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310765970.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing carbon fiber composite materials have low flame retardant properties, complex preparation of flame retardant resins, and the existing flame retardant has problems of environmental pollution and poor compatibility.

Method used

The nanocellulose-silicon suspension is prepared by mixing nanocellulose with silicon-based compounds and combined with resin material. The flame-retardant cellulose aerogel-reinforced resin material is prepared through freeze-drying and drying processes, avoiding powder and resin The mixing problem is that the aerogel flame retardant coating is constructed directly on the resin surface.

Benefits of technology

It significantly improves the flame retardant performance of composite materials, while maintaining the strength of the resin, low process cost, convenient process, and high temperature resistance and high strength.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a flame-retardant cellulose aerogel reinforced resin material as well as a preparation method and application thereof. The limit oxygen index of the resin material in air is 20%-50%. The preparation method comprises the following steps: mixing nanocellulose with deionized water, acidizing, and adding a silicon compound to obtain a cellulose-silicon suspension; and suspending a resin material sample strip in a mold, pouring the cellulose-silicon suspension into a gap between the resin material sample strip and the mold, freezing, demolding, drying and baking to obtain the cellulose-silicon composite material. The obtained resin material can be well applied to the fields of reinforced modified plastics, buildings, electric heating and heat insulation materials, and the flame retardant property of the composite material can be remarkably improved under the condition that the strength of the resin material is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogel flame retardant materials, and in particular to a flame retardant cellulose aerogel-reinforced resin material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the composite materials industry, carbon fiber-resin composite materials have been widely used in more and more fields, and the flame retardant properties of composite materials have become one of the obstacles to the use of composite materials. At present, most of the research on the flame retardancy of composite materials focuses on the flame retardant properties of resins, and there are certain problems with the existing flame retardant technology: the flame retardant properties of composite materials are mainly improved by adding various inorganic flame retardants, organic flame retardants, and inorganic / organic composite flame retardants to the resin, but inorganic flame retardants have large addition amounts, and organic flame retardants have environmental pollution problems. Organic / inorganic composite flame retardants have high flame retardant efficiency, but they also have poor compatibility and complex preparation processes. Green and environmentally friendly bio-based flame retardants have attracted people's attention.

[0003] Aerogel's excellent properties such as low density, low thermal conductivity, high porosity, and high specific surface area make it suitable for use as a flame retardant material. Existing aerogel flame retardant materials used in flame retardant processes are mostly inorganic aerogels, such as SiO 2 Aerogel has poor mechanical properties and is fragile, and SiO 2 The powder has an impact on the environment, which limits its application in flame retardancy.

[0004] Cellulose aerogel has the excellent properties of traditional aerogel materials and the advantages of cellulose being naturally renewable. It has been widely used in fields such as construction and aerospace, and is a special environmentally friendly material with great development potential. At present, physical blending or chemical modification methods are usually used to functionalize cellulose aerogels to prepare composite aerogels with special properties. Compared with inorganic aerogels, it has better flexibility, better compatibility with organic materials, and can firmly adhere to resin surfaces of any shape.

[0005] In order to solve the problems of low flame retardancy of existing carbon fiber composite materials and complex preparation of flame retardant resins, flame retardant cellulose aerogel is used as a flame retardant material to modify the resin, improve the flame retardancy, and simplify the preparation process of flame retardant composites. However, at present, the flame retardant modification method of flame retardant cellulose aerogel modified resin materials is an addition type, that is, powdered flame retardant is mixed with resin and solidified to form a flame retardant resin material. The flame retardant performance of this material depends on the increase in the amount of aerogel powder, and the interface performance between aerogel and resin, the particle size of powder, and the uniformity of distribution will have a great influence on the mechanical properties of resin. In order to achieve a certain flame retardant performance, aerogel powder needs to be increased in large quantities, but this will reduce the mechanical properties of the resin. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of low flame retardancy of resin materials in the prior art, and the inability to obtain both flame retardancy and mechanical strength, and to provide a flame retardant cellulose aerogel-reinforced resin material and a preparation method and application thereof. The composite material prepared by the method can significantly improve the flame retardancy of the composite material while maintaining the strength of the resin material. The preparation method is low in cost and convenient in process.

[0007] In order to achieve the above object, the present invention first provides a method for preparing a flame retardant cellulose aerogel-reinforced resin material, the method comprising the following steps:

[0008] S1. mixing nanocellulose with deionized water, acidifying it, and then adding a silicon compound to obtain a cellulose-silicon suspension;

[0009] S2. Hang the resin material sample in the mold, pour the cellulose-silicon suspension obtained in step S1 into the gap between the resin material sample and the mold, put the mold into a cold trap to freeze, demold, dry and bake the frozen sample to obtain a flame-retardant cellulose aerogel-reinforced resin material.

[0010] Further, step S1 includes the following sub-steps:

[0011] S11: After first mixing the nanocellulose and deionized water, stirring at a first speed for a first time to obtain a nanocellulose suspension;

[0012] S12: adding an acid solution to the nanocellulose suspension obtained in step S11 for a second mixing to adjust the pH value of the solution to obtain an acidified nanocellulose suspension;

[0013] S13: adding a silicon-based compound to the acidified nanocellulose suspension obtained in step S12 for a third mixing, and stirring at a third speed for a third time to obtain a cellulose-silicon suspension.

[0014] Preferably:

[0015] In step S11, the mass ratio of the nanocellulose to deionized water is (0.1-1):100; in the first mixing, the first speed is 500-4000 rpm, and the first stirring time is 1-5 hours.

[0016] In step S12, the acid solution is at least one of a hydrochloric acid aqueous solution or a sulfuric acid aqueous solution; there is no particular limitation on the concentration of the acid solution, as long as it can make the nanocellulose suspension reach a specific pH value. Preferably, the concentration of the acid solution is 0.01-1wt%; the pH value of the acidified nanocellulose suspension is 2-6.

[0017] In step S13, the silicon compound is selected from at least one of methyltrimethoxysilane and methyltriethoxysilane; the mass ratio of the silicon compound to the nanocellulose is (1-0.5): (0.5-1); in the third mixing, the third speed is 500-4000 rpm, and the third stirring time is 1-5 hours. The conditions of the first mixing and the conditions of the third mixing can be the same or different.

[0018] In step S2, the distance between the resin material strip and the mold is 0.8-1.2 mm.

[0019] In step S2, a freeze dryer is used to dry and bake the demoulded sample.

[0020] Secondly, the present invention also provides a flame-retardant cellulose aerogel-reinforced resin material prepared by the above-mentioned preparation method. The resin material has a limiting oxygen index of 20% to 50% in air, a UL-94 test grade of V-2 to V-0, and a tensile strength of 73 to 76 MPa.

[0021] Third, the present invention also provides the application of the flame-retardant cellulose aerogel-reinforced resin material, and the resin material can be applied to fields including but not limited to reinforced modified plastics, construction fields, electric heating fields, or thermal insulation materials.

[0022] In the present invention, cellulose aerogel flame retardant material is used as a coating to cover the surface of the carbon fiber composite material to improve the flame retardant properties of the carbon fiber composite material. Compared with other flame retardant coatings, the aerogel material is lighter; at the same time, compared with other aerogel flame retardant materials, cellulose aerogel material is low in price, environmentally friendly, and has better compatibility with the surface of the composite material. As the country's requirements for green, environmentally friendly and recycling are continuously increasing, green ecology will become the development trend of flame retardants.

[0023] However, in the current prior art, the flame retardant modification method of the flame retardant cellulose aerogel modified resin material is the addition type, that is, the powdered flame retardant is mixed with the resin and solidified to form a flame retardant resin material. The flame retardant performance of this material depends on the increase in the amount of aerogel powder, and the interface performance between the aerogel and the resin, the particle size of the powder, and the uniformity of the distribution will have a great influence on the mechanical properties of the resin. In order to achieve a certain flame retardant performance, aerogel powder needs to be increased in large quantities, which will reduce the mechanical properties of the resin. The present invention does not involve the problem of mixing powder and resin. It chooses to construct an aerogel flame retardant coating on the surface of the resin to improve the flame retardant performance of the resin. The strength of the resin is its own strength, and the coating will not affect the strength of the resin.

[0024] In summary, through the technical scheme and analysis, the flame-retardant cellulose aerogel-reinforced resin material and the preparation method and application thereof provided by the present invention can obtain the following beneficial technical effects:

[0025] (1) The method for preparing the flame-retardant cellulose aerogel-reinforced resin material provided by the present invention comprises compounding the flame-retardant cellulose aerogel and the resin, thereby making it possible to significantly improve the flame retardancy of the composite material while maintaining the strength of the resin.

[0026] (2) The preparation method is low-cost and has a convenient process.

[0027] (3) The flame-retardant cellulose aerogel-reinforced resin material prepared by the preparation method of the present invention has good integrity and is widely used in the market because of its high temperature resistance and high strength. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with specific examples, but the present invention is not limited to the following examples. The experimental methods used in the examples are conventional methods unless otherwise specified. The equipment, materials, etc. used in the examples, unless otherwise specified, can all be obtained from public commercial channels.

[0029] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0030] The present invention will be described in detail below by way of examples. In the following examples,

[0031] Flame retardant cellulose aerogel shell resin material According to ASTM D2863-2009 standard, the limiting oxygen index (LOI) of aerogel is tested using a limiting oxygen index tester. The aerogel sample is placed in a combustion chamber and the oxygen content in the atmosphere is adjusted to find the minimum oxygen concentration that can sustain combustion. Sample size: 130*10*4mm, each sample is tested 3 times.

[0032] Aerogel samples were subjected to vertical combustion (UL-94) test according to ASTM D3801 standard, sample size: 130*10*4mm, each test was performed 3 times.

[0033] The tensile test was conducted on a YF-900 computer tensile testing machine. At least three parallel samples were tested for each sample and the average value was taken. The test speed was 2.0 mm / min.

[0034] The raw materials used in the examples and comparative examples are all commercially available.

[0035] Example 1

[0036] A method for preparing a flame-retardant cellulose aerogel-reinforced resin material comprises the following steps:

[0037] 1) Preparation of nanocellulose-Si suspension: 0.5 g of nanocellulose and 100 mL of water were stirred and mixed at a rotation speed of 1500 rpm for 1 h, 0.01% hydrochloric acid was added to pH = 2, and then 0.25 g of methyltrimethoxysilane was added, and the mixture was stirred and mixed at a rotation speed of 1500 rpm for 1 h to obtain a nanocellulose-Si suspension.

[0038] 2) Preparation of flame-retardant cellulose aerogel-reinforced resin material: A resin strip of 130*10*4 mm was suspended in the center of a mold with a cross section of 12*6 mm, and the distance between the strip and the bottom of the mold was 1 mm. Nanocellulose-Si suspension was added to the gap between the mold and the strip, and the mold was frozen. After demolding, the strip was placed in a freeze dryer for drying, and the dried strip was placed in an oven for drying to obtain a flame-retardant cellulose aerogel-reinforced resin material strip A1. The performance parameters of the composite material A1 are shown in Table 1.

[0039] Example 2

[0040] A method for preparing a flame-retardant cellulose aerogel-reinforced resin material comprises the following steps:

[0041] 1) Preparation of nanocellulose-Si suspension: 0.1 g of nanocellulose and 100 mL of water were stirred and mixed at a rotation speed of 1500 rpm for 1 h, 0.01% hydrochloric acid was added to pH = 2, and then 0.05 g of methyltrimethoxysilane was added, and the mixture was stirred and mixed at a rotation speed of 1500 rpm for 1 h to obtain a nanocellulose-Si suspension.

[0042] 2) Preparation of flame-retardant cellulose aerogel-reinforced resin material: A resin strip of 130*10*4 mm was suspended in the center of a mold with a cross section of 12*6 mm, and the distance between the strip and the bottom of the mold was 1 mm. Nanocellulose-Si suspension was added to the gap between the mold and the resin strip, and the mold was frozen. After demolding, the strip was placed in a freeze dryer for drying, and the dried strip was placed in an oven for drying to obtain a flame-retardant cellulose aerogel-reinforced resin material strip A2. The performance parameters of the composite material A2 are shown in Table 1.

[0043] Example 3

[0044] A method for preparing a flame-retardant cellulose aerogel-reinforced resin material comprises the following steps:

[0045] 1) Preparation of nanocellulose-Si suspension: 0.5 g of nanocellulose and 100 mL of water were stirred and mixed at a rotation speed of 1500 rpm for 1 h, 0.01% hydrochloric acid was added to pH = 2, and then 0.5 g of methyltrimethoxysilane was added, and the mixture was stirred and mixed at a rotation speed of 1500 rpm for 1 h to obtain a nanocellulose-Si suspension.

[0046] 2) Preparation of flame-retardant cellulose aerogel-reinforced resin material: A resin strip of 130*10*4 mm was suspended in the center of a mold with a cross section of 12*6 mm, and the distance between the strip and the bottom of the mold was 1 mm. Nanocellulose-Si suspension was added to the gap between the mold and the resin strip, and the mold was frozen. After demolding, the strip was placed in a freeze dryer for drying, and the dried strip was placed in an oven for drying to obtain a flame-retardant cellulose aerogel-reinforced resin material strip A3. The performance parameters of the composite material A3 are shown in Table 1.

[0047] Example 4

[0048] A method for preparing a flame-retardant cellulose aerogel-reinforced resin material comprises the following steps:

[0049] 1) Preparation of nanocellulose-Si suspension: 1 g of nanocellulose and 100 mL of water were stirred and mixed at a speed of 1500 rpm for 1 h, 0.01% hydrochloric acid was added to pH = 2, and then 2 g of methyltrimethoxysilane was added, and the mixture was stirred and mixed at a speed of 1500 rpm for 1 h to obtain a nanocellulose-Si suspension.

[0050] 2) Preparation of flame-retardant cellulose aerogel-reinforced resin material: A resin strip of 130*10*4 mm was suspended in the center of a mold with a cross section of 12*6 mm, and the distance between the strip and the lower end of the mold was 1 mm. Nanocellulose-Si suspension was added to the gap between the mold and the resin strip, and the mold was frozen. After demolding, the strip was placed in a freeze dryer for drying, and the dried strip was placed in an oven for drying to obtain a flame-retardant cellulose aerogel-reinforced resin material strip A4. The performance parameters of the composite material A4 are shown in Table 1.

[0051] Example 5

[0052] A method for preparing a flame-retardant cellulose aerogel-reinforced resin material comprises the following steps:

[0053] 1) Preparation of nanocellulose-Si suspension: 0.5 g of nanocellulose and 100 mL of water were stirred and mixed at 500 rpm for 5 h, 0.1% sulfuric acid was added to pH = 4, and 0.5 g of methyltrimethoxysilane was added, and the mixture was stirred and mixed at 500 rpm for 5 h to obtain a nanocellulose-Si suspension.

[0054] 2) Preparation of flame-retardant cellulose aerogel-reinforced resin material: A resin strip of 130*10*4 mm was suspended in the center of a mold with a cross section of 12*6 mm, and the distance between the strip and the bottom of the mold was 0.8 mm. Nanocellulose-Si suspension was added to the gap between the mold and the resin strip, and the mold was frozen. After demolding, the strip was placed in a freeze dryer for drying, and the dried strip was placed in an oven for drying to obtain a flame-retardant cellulose aerogel-reinforced resin material strip A3. The performance parameters of the composite material A3 are shown in Table 1.

[0055] Example 6

[0056] A method for preparing a flame-retardant cellulose aerogel-reinforced resin material comprises the following steps:

[0057] 1) Preparation of nanocellulose-Si suspension: 1 g of nanocellulose and 100 mL of water were stirred and mixed at 4000 rpm for 2 h, 1% sulfuric acid was added to pH = 6, and then 2 g of methyltriethoxysilane was added, and the mixture was stirred and mixed at 4000 rpm for 2 h to obtain a nanocellulose-Si suspension.

[0058] 2) Preparation of flame-retardant cellulose aerogel-reinforced resin material: A resin strip of 130*10*4 mm was suspended in the center of a mold with a cross section of 12*6 mm, and the distance between the strip and the lower end of the mold was 1.2 mm. Nanocellulose-Si suspension was added to the gap between the mold and the resin strip, and the mold was frozen. After demolding, the strip was placed in a freeze dryer for drying, and the dried strip was placed in an oven for drying to obtain a flame-retardant cellulose aerogel-reinforced resin material strip A4. The performance parameters of the composite material A4 are shown in Table 1.

[0059] Comparative Example 1

[0060] Directly use the resin specimen of 130*10*4mm for testing.

[0061] Comparative Example 2

[0062] 1) Preparation of nanocellulose-Si suspension: 0.5 g of nanocellulose and 100 mL of water were stirred and mixed at a rotation speed of 1500 rpm for 1 h to obtain a nanocellulose-Si suspension.

[0063] 2) Preparation of flame-retardant aerogel shell: A resin strip of 130*10*4mm was suspended in the center of a mold with a cross section of 12*6mm, and the distance between the strip and the lower end of the mold was 1mm. Nanocellulose-Si suspension was added to the gap between the mold and the resin strip, and the mold was frozen. After demolding, the strip was placed in a freeze dryer for drying, and the dried strip was placed in an oven for drying to obtain a flame-retardant cellulose aerogel shell resin material strip D2. The performance parameters of the composite material D2 are shown in Table 1.

[0064] Table 1 Various indicators of embodiments and comparative examples

[0065] Sample name Limiting oxygen index (%) UL-94 Tensile strength(MPa) Example 1 32.0 V-1 74.5 Example 2 25.5 V-2 73.9 Example 3 35.7 V-1 75.2 Example 4 40.4 V-0 75.8 Example 5 38.5 V-1 74.7 Example 6 49.7 V-0 75.4 Comparative Example 1 17.3 Fail 73.6 Comparative Example 2 20.3 V-2 74.1

[0066] Compared with comparative example 1, the flame retardant cellulose aerogel-reinforced resin materials prepared in Examples 1-6 of the present invention have better flame retardant properties. With the increase of the amount of cellulose in the aerogel shell and the proportion of silicon in the aerogel, the flame retardant properties of the flame retardant cellulose aerogel-reinforced resin material strips also increase. The limiting oxygen index and UL-94 of Example 4 reach 40.4% and pass the V-0 test of UL-94, respectively. The limiting oxygen index and UL-94 of Example 6 reach 49.7% and pass the V-0 test of UL-94, respectively, which are much higher than those of comparative examples 1 and 2. At the same time, while the flame retardant properties are improved, the tensile strength of the flame retardant cellulose aerogel-reinforced resin material strips does not change significantly, and even slightly increases. The addition of the flame retardant cellulose aerogel shell can significantly improve the flame retardant properties of the flame retardant cellulose aerogel-reinforced resin material strips, and keep the tensile strength of the flame retardant cellulose aerogel-reinforced resin material strips unchanged, so that the flame retardant cellulose aerogel-reinforced resin material has a wider application.

[0067] The flame-retardant cellulose aerogel-reinforced resin material provided by the present invention can be used as a material with high efficiency in improving flame retardancy in reinforced and modified plastics, the construction field, the electric heating field and thermal insulation materials.

[0068] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a flame-retardant cellulose aerogel-reinforced resin material, characterized in that: The following steps are involved: S1. mixing nanocellulose with deionized water, acidifying it, and then adding a silicon compound to obtain a cellulose-silicon suspension; S2. Hang the resin material sample in the mold, pour the cellulose-silicon suspension obtained in step S1 into the gap between the resin material sample and the mold, put the mold into a cold trap to freeze, demold, dry and bake the frozen sample to obtain a flame-retardant cellulose aerogel-reinforced resin material.

2. The method for preparing the flame-retardant cellulose aerogel-reinforced resin material according to claim 1, characterized in that: In step S1, The following steps are included: S11: After first mixing the nanocellulose and deionized water, stirring at a first speed for a first time to obtain a nanocellulose suspension; S12: adding an acid solution to the nanocellulose suspension obtained in step S11 for a second mixing to adjust the pH value of the solution to obtain an acidified nanocellulose suspension; S13: adding a silicon-based compound to the acidified nanocellulose suspension obtained in step S12 for a third mixing, and stirring at a third speed for a third time to obtain a cellulose-silicon suspension.

3. The method for preparing a flame-retardant cellulose aerogel-reinforced resin material according to claim 1 or 2, characterized in that: In step S11, the mass ratio of the nanocellulose to deionized water is (0.1-1):

100.

4. The method for preparing a flame-retardant cellulose aerogel-reinforced resin material according to claim 1 or 2, characterized in that: In step S11, in the first mixing, the first speed rotation speed is 500-4000 rpm, and the first stirring time is 1-5 hours.

5. The method for preparing a flame-retardant cellulose aerogel-reinforced resin material according to claim 1 or 2, characterized in that: In step S12, the acid solution is at least one of a hydrochloric acid aqueous solution or a sulfuric acid aqueous solution, and the concentration of the acid solution is 0.01-1 wt%.

6. The method for preparing a flame-retardant cellulose aerogel-reinforced resin material according to claim 1 or 2, characterized in that: In step S12, the pH value of the acidified nanocellulose suspension is 2-6.

7. The method for preparing a flame-retardant cellulose aerogel-reinforced resin material according to claim 1 or 2, characterized in that: In step S13, the silicon-based compound is selected from at least one of methyltrimethoxysilane and methyltriethoxysilane.

8. The method for preparing a flame-retardant cellulose aerogel-reinforced resin material according to claim 1 or 2, characterized in that: In step S13, the mass ratio of the silicon compound to the nanocellulose is (1-0.5):(0.5-1).

9. The method for preparing a flame-retardant cellulose aerogel-reinforced resin material according to claim 1 or 2, characterized in that: In step S13, in the third mixing, the third speed rotation speed is 500-4000 rpm, and the third stirring time is 1-5 hours.

10. The method for preparing a flame-retardant cellulose aerogel-reinforced resin material according to claim 1, characterized in that: In step S2, the distance between the resin material strip and the mold is 0.8-1.2 mm.

11. The method for preparing a flame-retardant cellulose aerogel-reinforced resin material according to claim 1, characterized in that: In step S2, a freeze dryer is used to dry and bake the demoulded sample.

12. The flame-retardant cellulose aerogel-reinforced resin material prepared by the preparation method according to any one of claims 1 to 11, characterized in that: The resin material has a limiting oxygen index of 20% to 50% in air, a UL-94 test grade of V-2 to V-0, and a tensile strength of 73 to 76 MPa.

13. The use of the flame-retardant cellulose aerogel-reinforced resin material according to claim 12, characterized in that: The resin material is used in reinforced modified plastics, construction field, electric heating field or thermal insulation material field.

Citation Information

Cited By

  • Composite cellulose aerogel as well as preparation method and application thereof

    CN120098319A